2016
DOI: 10.1097/aog.0000000000001508
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Biomarkers in Women With Suspected Preeclampsia in a Prospective Multicenter Study

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…One isoform that seems to be gaining more widespread acceptance at least as a predictive marker in PE is circulating PlGF (which preferentially binds VEGFR1). In PE, PlGF levels are decreased, whether free or sFlt-1 bound (Levine et al 2004; Robinson et al 2006) Certainly recent prospective trials suggest the sFlt:PlGF ratio may have particular value as a predictive marker (Zeisler et al 2016) while another study suggests a single marker (PlGF, sFlt-1 or endoglin) may be effective (Duckworth et al 2016). Others have reported the predictive value even at 20–34 weeks were limited (Andersen et al 2016).…”
Section: Hormones Of Preeclampsia-related Endothelial Dysfunctionmentioning
confidence: 99%
“…One isoform that seems to be gaining more widespread acceptance at least as a predictive marker in PE is circulating PlGF (which preferentially binds VEGFR1). In PE, PlGF levels are decreased, whether free or sFlt-1 bound (Levine et al 2004; Robinson et al 2006) Certainly recent prospective trials suggest the sFlt:PlGF ratio may have particular value as a predictive marker (Zeisler et al 2016) while another study suggests a single marker (PlGF, sFlt-1 or endoglin) may be effective (Duckworth et al 2016). Others have reported the predictive value even at 20–34 weeks were limited (Andersen et al 2016).…”
Section: Hormones Of Preeclampsia-related Endothelial Dysfunctionmentioning
confidence: 99%
“…71 In the second trimester, low levels of PlGF have superior screening performance in comparison with many potential biomarkers to predict placenta-related complications. 84 In a prospective cohort of 274 women with suspected preeclampsia presenting at 20-34 weeks' gestation, low circulating PlGF (<100 pg/mL) had high sensitivity to detect SGA births (n ¼ 96) below third customized birthweight centile (sensitivity 93%, negative predictive value [NPV] 90%), which was superior to fetal weight estimation by ultrasound (sensitivity 71%, NPV 79%). 85 An earlier multicenter study by the same group, of 592 women with reduced symphysisfundal height measurements, found that combining PlGF with ultrasound biometry increased the sensitivity from 58-69% for the detection of customized growth at the third centile (with the same 93% NPV).…”
Section: Circulating Proangiogenic and Antiangiogenic Placenta-derivementioning
confidence: 99%
“…In Table 1 we report a summary of the studies that aimed to understand if PCT is a PE marker [49,[52][53][54][55][59][60][61][62][63]. At present, however, there are no plasmatic factors that can be considered PE markers with a predictive value.…”
Section: Review Series: Immunology Of Pregnancymentioning
confidence: 99%
“…Perhaps for this reason, numerous studies have been carried out during the last 5 years to verify if the PCT could be an ideal candidate for this role. In Table 1 we report a summary of the studies that aimed to understand if PCT is a PE marker [49,[52][53][54][55][59][60][61][62][63]. In general, we can deduce that PCT plasmatic levels are increased in PE and its levels correlate with the severity of the disease, but PCT has no predictive value.…”
Section: Review Series: Immunology Of Pregnancymentioning
confidence: 99%